Topika afektownej skromności w wybranych wystąpieniach sejmowych Adama Kazimierza Czartoryskiego - Gonera, Marzena (Collectanea Philologica, 2019)
The main aim of the article is to present ways of expressing one of the most important means of reasoning – namely, the topos of exaggerated modesty – in selected parliamentary speeches by Adam Kazimierz Czartoryski. The considerations are focused on indicating its sources, definitions, functions and variants. The most important method used to explore the topic will be rhetorical analysis. In addition, the author indicates the relationship between the topos of exaggerated modesty and language etiquette.